The treatise on the knowledge about the rational soul and its states by Ibn Sina: a critical edition and annotated translation - Mostafa Kamal Mokhtar (Universiti Kebangsaan Malaysia, 1994)
Please refer fulltext/Sila rujuk teks penuh